2015
DOI: 10.1038/ncomms7991
|View full text |Cite
|
Sign up to set email alerts
|

Integrated digital inverters based on two-dimensional anisotropic ReS2 field-effect transistors

Abstract: Semiconducting two-dimensional transition metal dichalcogenides are emerging as top candidates for post-silicon electronics. While most of them exhibit isotropic behaviour, lowering the lattice symmetry could induce anisotropic properties, which are both scientifically interesting and potentially useful. Here we present atomically thin rhenium disulfide (ReS2) flakes with unique distorted 1T structure, which exhibit in-plane anisotropic properties. We fabricated monolayer and few-layer ReS2 field-effect transi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
351
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 537 publications
(394 citation statements)
references
References 39 publications
25
351
4
2
Order By: Relevance
“…Liu et al observed that the anisotropic ReS 2 ‐based FET under a fixed source–drain bias voltage of 100 mV had a large on/off ratio of 10 7 and low subthreshold swings of 100 mV dec −1 (Figure 6g), when the back gate was swept from −50 to 50 V. The anisotropic mobility ratio µm ax /µm in along two principle axes of this device is 3.1, which is better than that of a device containing few‐layer black phosphorus (Figure 6h) 27, 41. The direction of lowest mobility (0° or 180°) was defined as the reference direction, and the highest mobility of 15.4 cm 2 V −1 s −1 was measured in a six‐layer device in the 120° (or 300°) direction (Figure 6i) 67…”
Section: Applications For 2d Optoelectronic and Electronic Devicesmentioning
confidence: 86%
See 2 more Smart Citations
“…Liu et al observed that the anisotropic ReS 2 ‐based FET under a fixed source–drain bias voltage of 100 mV had a large on/off ratio of 10 7 and low subthreshold swings of 100 mV dec −1 (Figure 6g), when the back gate was swept from −50 to 50 V. The anisotropic mobility ratio µm ax /µm in along two principle axes of this device is 3.1, which is better than that of a device containing few‐layer black phosphorus (Figure 6h) 27, 41. The direction of lowest mobility (0° or 180°) was defined as the reference direction, and the highest mobility of 15.4 cm 2 V −1 s −1 was measured in a six‐layer device in the 120° (or 300°) direction (Figure 6i) 67…”
Section: Applications For 2d Optoelectronic and Electronic Devicesmentioning
confidence: 86%
“…The distance between these dimerized Re atoms can be even shorter than that in rhenium single crystals97; thus, the total energy and symmetry of the system are reduced 40. This is a major origin of the strong anisotropic properties of ReSe 2 and ReS 2 validated by Liu et al67 The in‐plane anisotropic properties of monolayer and few‐layered ReS 2 are shown in Figure 1c, ReS 2 has two principal axes, ( a axis, 118.97°; b axis, 61.03°). In accordance with the angles of the a and b axes, a quadrilateral shape with an angle of ≈60° or 120° is observed in thin, exfoliated ReS 2 , and the large anisotropic ratio of mobility of ReS 2 along the two axes (up to 3.1) is the highest of all studied layered 2D materials.…”
Section: Anisotropic Crystalline Structurementioning
confidence: 99%
See 1 more Smart Citation
“…and group III–VI nanomaterials (InSe,38, 39, 40, 41, 42 GaSe,43, 44, 45, 46, 47, 48 etc.) have been extensively investigated in many fields including photodetectors,49, 50, 51, 52, 53, 54, 55, 56, 57, 58 gas sensors,59, 60 field effect transistors (FETs),38, 61, 62, 63, 64, 65 and flexible devices 66, 67, 68…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The class of van der Waals layered semiconductors with in-plane anisotropy is a topic of great current interest and, besides ReS 2 and ReSe 2 , it includes black phosphorus, [5][6][7] GeS, 8 transition metal trichalcogenides 9 and Sb 2 Se 3 . 10 Proposed applications of ReX 2 (X = S, Se) include plasmonic materials, 11 polarization-sensitive photodetectors with high sensitivity, [12][13][14][15] inverters, 16 catalytic devices, 17,18 and few-layer field effect 19,20 or heterojunction 21 transistor structures. The anisotropy of the ReX 2 compounds arises because, instead of adopting the octahedral (2H) or trigonal (1T) polymorphs typical of TMDs, they undergo a distortion to form a trigonal 1T′ polymorph.…”
Section: Introductionmentioning
confidence: 99%